On-chip mid-infrared photothermoelectric detectors for full-Stokes detection - Dai Mingjin (2022)
On-chip polarimeters are highly desirable for the next-generation ultra-compact optical and optoelectronic systems. Polarization-sensitive photodetectors relying on anisotropic absorption of natural/artificial materials have emerged as a promising candidate for on-chip polarimeters owing to their filterless configurations. However, these photodetectors can only be applied for detection of either linearly or circularly polarized light, not applicable for full-Stokes detection. Here, we propose and demonstrate three-ports polarimeters comprising on-chip chiral plasmonic metamaterial-mediated mid-infrared photodetectors for full-Stokes detection. By manipulating the spatial distribution of chiral metamaterials, we could convert polarization-resolved absorptions to corresponding polarization-resolved photovoltages of three ports through the photothermoelectric effect. We utilize the developed polarimeter in an imaging demonstration showing reliable ability for polarization reconstruction. Our work provides an alternative strategy for developing polarization-resolved photodetectors with a bandgap-independent operation range in the mid-infrared.